Comparative Analysis of CO₂ Content in Biogas and Synthetic Gas Using Chittick Titration Validated by Gas Chromatography - Pambudi, Alfian Wisnu; Rahmawati, Yeni; Taufany, Fadlilatul; Altway, Ali; Susianto (Eksergi, 2025)
This study aimed to validate the Chittick titration method for measuring carbon dioxide (CO2) content using gas chromatography (GC) as the reference method. Two types of gas samples were analyzed: synthetic CO2/N2 gas with a theoretical composition of 40:60 and biogas produced by anaerobic fermentation. Analyses were conducted in parallel using both methods to compare CO2 measurements. For synthetic gas, the Chittick titration recorded an average CO2 content of 39.11%, whereas GC recorded 40.52%. For biogas, Chittick titration produced 30.16%, whereas GC measured 31.40%. The differences between the methods were 0.81% for synthetic gas and 1.55% for biogas, with relative errors of 2.00% and 3.45%, respectively. The t-test results showed statistically significant differences (p < 0.05) between the methods for both gas types. However, the observed deviations remained within practically acceptable limits for small-scale laboratory applications. These findings suggest that Chittick titration is a practical and cost-effective alternative for estimating CO2 content, particularly in laboratories with limited access to gas chromatography equipment. This study is expected to serve as a useful reference for educational institutions and small laboratories that are seeking to develop simple gas analysis methods with adequate validity.